THE USE SIMPLE PAST TENSE AND CONJUNCTION IN RECOUNT TEXTS - Novia Setiani; Gustaman Saragih (INFERENCE: Journal of English Language Teaching, 2020)
The objective of this research is to find, to describe and to interpret the use of past verbs and conjunctions in recount texts, written by students of senior high school in Jakarta. The population in this research was the students of grade X at those two schools, meanwhile, the number of the population consists of 1400 students. Thus, the sample of the research was 10% from the population from which 140 students was taken. The method used in this recount texts. The result of this research is: first, Students’ mastery in using past verbs in writing recount texts is quite good; even though, there were some mistakes such as generalization; for instance, adding -ed ending for irregular verbs and using past verbs after prepositions; second, students’ mastery in using conjunctions was good and students could apply them in their writing correctly.Keywords: simple past tense; conjunction; recount text; foreign language writing